2010
DOI: 10.1111/j.1365-3180.2010.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed‐poplar competition dynamics and yield loss in Italian short‐rotation forestry

Abstract: In recent years there has been increasing interest in short-rotation poplar plantations for biomass production and cropping techniques and weed control strategies are being developed. Slow initial poplar growth can favour weed infestation and so there is a need for appropriate timing of weed control, based on an understanding of the competitive relationship and dynamics between poplar and weeds. A field experiment with annual and biennial crop cycles was conducted over two years. A 35 cm wide within-row weedy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
2
22
0
2
Order By: Relevance
“…However, as the area requirements for bioenergy feedstock production increases, the pressure on marginal sites or fallow grounds with unfavorable site conditions may increase and SRC systems applied here may also have negative environmental impacts. Most importantly, it seems that SRC plots have to be optimally prepared by plowing to guarantee weed control during crop establishment [8][9][10]. Especially on fallow grounds, this may lead to an extra emission of CO 2 and N 2 0.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the area requirements for bioenergy feedstock production increases, the pressure on marginal sites or fallow grounds with unfavorable site conditions may increase and SRC systems applied here may also have negative environmental impacts. Most importantly, it seems that SRC plots have to be optimally prepared by plowing to guarantee weed control during crop establishment [8][9][10]. Especially on fallow grounds, this may lead to an extra emission of CO 2 and N 2 0.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, establishment of poplar should be performed at this time as poplar is sensitive to competing vegetation [7,10,12]. A newly transplanted plant needs time to recover from the stress of handling and moving and establish roots to uptake soil water and nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…However, poplar plantings on forest land are not always successful. Poplar plantations may fail due to poor vegetation control or soil management as young poplars are sensitive to competing vegetation [7,10,12]. Poplars are fast growing, with a rotation period of 10 to 25 years depending on planting density and location [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that hybrid poplar shows considerable sensitivity to competition from herbaceous species, with disproportionately large effects on trees less than four years of age (Buhler et al 1998, Shock et al 2002, Pinno and Belanger 2009, Otto et al 2010. Competition effects also vary depending on the identity and abundance of competitors, and generally results in a loss of tree biomass and altered crown morphology (Marino andGross 1998, Kabba et al 2007).…”
Section: Introductionmentioning
confidence: 99%